CONTRIBUTION OF PAULO FREIRE’S THOUGHT: AN EDUCATOR BEYOND HIS TIME - Araujo de Luna, Erica; Santiago de Lima, Erivania; de Fátima Rodrigues de Oliveira, Luisa; de Meneses Silva, Ricardo; Coutinho de Souza, Rubiana (Revista Gênero e Interdisciplinaridade, 2022)
The primary scope of the work is to highlight important points about Paulo Freire’s influence on education. Thus, the research aims to analyze and interpret the contribution of Paulo Freire’s thought in the Brazilian teaching process. The methodology used privileges the approach of a qualitative nature and chooses, as an investigative procedure, the bibliographic study. It was noticed, in the face of the study, that Freire’s thinking contributes in a relevant way to education professionals in their daily educational practices, since he sought a scenario that would pass the dialogue so that all education actors had autonomy in their relationships. . It is worth remembering that the results obtained according to this research confirm that this theorist was openly advocating that education should awaken the criticality of the student, causing him to seek the expansion of his social conscience and achieve autonomy. Therefore, it is concluded that Paulo Freire fought for the construction of Brazilian education, and left a legacy of hope for possible social transformations. It is expected that Paulo Freire’s political-pedagogical thought is always in motion and dialogues with different contemporary issues.